FENOMENA ROB SEMARANG SEBAGAI SUMBER BELAJAR IPS (Universitas Negeri Semarang, 2017)
The use of rob flood learning resources in the learning activities can make the students become more active and motivated in following the learning, but the need for more control of the teacher because at the time of the learning activities took place some students discuss outside the learning materials. The utilization of Rob Flood learning resources can have a positive impact on student competence (understanding, attitude and skills) of students. This is because the students are faced with real object of study, so that the material mismatch can be simplified by the learning source, the broad environmental learning source can represent what the teacher is unable to say through certain words, even the material abilities can be concretized by the presence of the source Learning it. Penggunaan banjir rob sebagai sumber dalam kegiatan pembelajaran dapat membuat para siswa menjadi lebih aktif dan termotivasi dalam mengikuti proses pembelajaran, tetapi membutuhkan lebih banyak control dari guru, karena kegiatan pembelajaran berada di luar kelas. Pemanfaatan sumber belajar banjir Rob dapat memiliki dampak positif pada kompetensi siswa (pemahaman, sikap dan keterampilan). Hal ini karena siswa dihadapkan pada proses pembelajaran dengan objek nyata, sehingga ketimpangan materi dapat disederhanakan dengan sumber pembelajaran, sumber pembelajaran lingkungan yang luas dapat mewakili materi yang tidak dapat disampaikan hanya dengan menggunakan kalimat atau deskripsi dari guru. Melalui sumber belajar ini materi tentang banjir rob dapat disampaikan secara lebih konkret.